Pengaruh Penggunaan Media Pembelajaran Tiktok Terhadap Keterampilan Mengajar Mahasiswa PGMI UNHASY - Siti Rofi’ah; Laily Masruroh (STKIP Andi Matappa Pangkep, 2022)
Online learning during The Covid-19 Pandemic requires lectures creativity to use learning media that are appropriate to the situation and condition. The purpose of this study is to optimize online learning by using social media tiktok and to describe the effect of using tiktok learning media on students' learning skill. The population in this study was all 4th student of the PGMI UNHASY at Jombang. Data collection is done by providing a questionnaire at google form. The data analysis technique used descriptive statistics and inferential statistic analysis. The result showed that the average use of social media tiktok was 27,97 and the percentage 40% in a good enough category. And the result of teaching skills with an average 46,27 And percentage 37% in the low category. The results of inferential statistic analysis obtained Rcount 0,58>Rtable 0,58 at a significance level of 0,05%, thus H0 is rejected and H1 accepted. The conclusion in this study is that there is a significant effect between the use of social media tiktok with the teaching skill of students of PGMI UNHAS study Program at Jombang.